2015
DOI: 10.1007/s10681-015-1579-9
|View full text |Cite
|
Sign up to set email alerts
|

Can achene selection in sunflower crop–wild hybrids by pre-dispersal seed predators hasten the return to phenotypically wild sunflowers?

Abstract: Bird attack is a serious limitation to sunflower yield in several regions of the world, but it could also cause selection. The wild Helianthus annuus, naturalized in several regions of the world, hybridizes with the crop and produces crop-wild offspring. It is unknown how the selective force of seed predation by birds could drive evolution after a hybridization event. After two generations of natural selection exerted by birds (mostly by Eared Dove and Monk Parakeets), achene and plant traits of the cropwild h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In undisturbed habitats, seeds may suffer from greater predation that could limit establishment in suitable habitats (Alexander and Schrag 2003;Chauhan et al 2006;Kröel-Dulay et al 2019). In our conditions, birds were possibly the main seed predators (Presotto et al 2016) and they were also seen on the plots after the initiation of the experiment (first author´s observation). Previous studies have found differential sunflower predation associated with seed size (i.e.…”
Section: Seed Emergence Increase With Disturbancementioning
confidence: 78%
See 1 more Smart Citation
“…In undisturbed habitats, seeds may suffer from greater predation that could limit establishment in suitable habitats (Alexander and Schrag 2003;Chauhan et al 2006;Kröel-Dulay et al 2019). In our conditions, birds were possibly the main seed predators (Presotto et al 2016) and they were also seen on the plots after the initiation of the experiment (first author´s observation). Previous studies have found differential sunflower predation associated with seed size (i.e.…”
Section: Seed Emergence Increase With Disturbancementioning
confidence: 78%
“…Previous studies have found differential sunflower predation associated with seed size (i.e. larger seeds were eaten preferentially) (Alexander et al, 2001;Presotto et al, 2016) and/or oil content (i.e. seed with more oil content were eaten preferentially) (Dechaine et al 2010).…”
Section: Seed Emergence Increase With Disturbancementioning
confidence: 99%
“…Most of these traits are considered "maladaptive" in noncultivated environments, and this could be one of the reasons for the low fitness seen in most crop-wild hybrids (Mercer, Wyse, & Shaw, 2006;Snow, Moran-Palma, Rieseberg, Wszelaki, & Seiler, 1998;Spencer & Snow, 2001;Zhi, Lu, Wang, & Jia, 2004). However, some crop-like traits, such as large leaves, numerous inflorescences and seeds, rapid growth, and self-compatibility, can be favorable in a range of environments (Arnaud, Fénart, Cordellier, & Cuguen, 2010;Baack, Sapir, Chapman, Burke, & Rieseberg, 2008;Dechaine et al, 2009;Mercer, Andow, Wyse, & Shaw, 2007), while others may increase susceptibility to herbivory (Alexander, Cummings, Kahn, & Snow, 2001;Dechaine et al, 2009;Presotto, Pandolfo, Poverene, & Cantamutto, 2016). Thus, introgression of crop-like traits into wild populations may be beneficial or detrimental depending on the trait and the species.…”
Section: Introductionmentioning
confidence: 99%
“…2001; Presotto et al . 2016). Second, in the soil seed bank, seed persistence is influenced by seed characteristics (seed size, dormancy, longevity), by local climate (temperature, humidity) and by external factors such as human disturbance with agricultural machinery (Presotto et al .…”
Section: Discussionmentioning
confidence: 99%